Socioecological Approach to Understanding Overnutrition Among Married and Cohabiting Women in Nigeria - Badru, Oluwaseun Abdulganiyu; Alabi, Tunde Adeyemo; Enwerem, Kenneth (Journal of Population and Social Studies [JPSS], 2024)
Overweight and obesity are currently an epidemic affecting both developed and developing countries. Sub-Saharan Africa has a double burden of being underweight and obese and has recently been battling an alarming increase in the prevalence of overweight. This study investigates the predictors of overnutrition among married women of reproductive age in Nigeria using the socioecological model (SEM) as a framework. The study hypothesizes that the Southern region will have a higher burden of overnutrition than the Northern region. The 2018 Nigeria Demographic and Health Survey (NDHS) was analyzed. A total of 8,531 non-pregnant married women met the inclusion criteria. Hierarchical multilevel logistic regression models were fitted, informed by the SEM framework. The occurrence of overnutrition was found to be 31.4%, with regional variations showing 31.7% in the South and 31.3% in the North. When all covariates were fitted in a model, being older, being a Christian, having tertiary education, having an older partner with tertiary education, being wealthy, and living in the urban area were predictors of overnutrition in multivariate analysis. Overnutrition among Nigerian married women was high, especially in the Southern region. Predictors of overweight are at all the SEM levels; therefore, it is better to consider all the levels when planning public health interventions.